Analysis of Service Quality for CPNS Basic Training Providers (LatSar) at BPSDM Jambi Province in 2019 - Musfarita Affiani (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2020)
The background of the research is the ineffectiveness of training which resulted in the low satisfaction of the training participants. Service quality includes reliability, responsiveness, assurance, empathy and tangibility. Efforts to improve service quality can be improved through service provision by referring to the dimensions of reliability, responsiveness, assurance, empathy and tangible, where assurance and empathy can be used as efforts to improve the quality of services that are more optimal for Finance. The aim of the research is to analyze the level of training management servqual. The analysis used is servqual analysis. The analysis of servqual on the management of the training showed that there was a significant gap between the trainee’s expectation with the training management.